Olive oil increase catalase activity and gluthatione peroxidase level in hyperglycemic rats - Ariani Zaltin Okvenda; Eti Yerizel; Raveinal (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Diabetes mellitus is the most common endocrine disease globally. Hyperglycemia in diabetes mellitus is known to trigger oxidative stress. The activity of glutathione peroxidase (GSH-Px) is decreased in diabetic conditions. Catalase activity acts as a defense system to prevent the formation of free radicals (oxidants) in the human body. Objective: This study aimed to determine the effectiveness of olive oil antioxidants on catalase activity and GSH-Px levels in hyperglycemic rats. Methods: Adult male Wistar rats were randomized into three groups (n: 8): untreated control (Control), alloxan-induced untreated (Alloxan), and alloxan-induced treatment (Treatment) of olive oil at 25 mL/day for 14 days. Catalase activities were measured using the spectrophotometry method, and GSH-Px levels were analyzed using an enzyme-linked immunosorbent assay (ELISA). Results: Administration of olive oil increased catalase activity compared to the untreated group in alloxan-induced rats. The average level of glutathione peroxidase was higher in the treatment group than in alloxan-induced rats. Conclusion: Antioxidants in olive oil increased catalase activity and glutathione peroxidase levels in alloxan-induced hyperglycemic rats.